Missed opportunities : the Philippine economy 1970-1994 - Romero, Rodolfo V. (Quezon City : Phoenix Publishing House, 1995)
A selection of articles written for The Manila Bulletin
Keywords: Philippines -- Economic conditions -- 1945-.; Philippines -- Economic policy